Advances and trends in weed management: A comprehensive review - Aparna, M V; Baskaran, R; Harisudan, C; Kalpana, R; Boominanthan, P; Jaghadeeswaran, R (Plant Science Today, 2025)
Weed management is a critical aspect of agricultural practices that can significantly impact crop yield and quality. As traditional methods face challenges such as herbicide resistance and environmental concerns, the agricultural sector is witnessing a shift towards innovative strategies for weed control. This review explores the emerging trends in weed management, focusing on sustainable and efficient approaches. Among them, one prominent trend is the adoption of agro ecological weed management strategies, which combine various control methods such as cultivation techniques, mechanical techniques, biological control and reasonable herbicide use. This approach minimizes reliance on herbicides while maximizing weed suppression and preserving natural ecosystems. Another significant trend is developing and utilizing precision agriculture technologies for targeted weed control techniques such as satellite imaging, unmanned aerial vehicles (UAVs) and sensor-based systems. These innovations enable farmers to accurately identify and manage weeds, reducing herbicide usage and minimizing environmental impact. Furthermore, the exploration of alternative weed control methods, including thermal, electrical and microwave-based technologies, is gaining momentum. These non-chemical approaches offer potential solutions to herbicide-resistant weeds and contribute to sustainable agricultural practices. Moreover, the integration of advanced breeding techniques and biotechnology for developing herbicide-resistant crops and enhancing allelopathic traits presents promising avenues for long-term weed management. In conclusion, this review highlights emerging technology for dealing with major problems, including increased understanding of weed biology linked with genomics; novel herbicide-resistant crops and redesigned weed-competing crops; multi-target herbicides; and enhanced biocontrol agents. When combined, these strategies could make up the elements of the next integrated packages designed to impede the emergence of new weed issues.